Xhosa narrative : an analysis of the production and linguistic properties of discourse with particular reference to "iintsomi" texts - Gough, David Huw (Rhodes University, Faculty of Humanities, School of Languages, 1986)
Although the areas I intend to investigate are rather diverse, what unites them is a concern for the ancient and fascinating question of the relationship between language and thought. Assumptions concerning the latter are surely latent as the basis for any inquiry into language. One of my general purposes is to give some overt orientation to this problem which is all too often simply glossed over. More particularly, I am also concerned with shaping a new approach to Bantu linguistic inquiry in terms of an emphasis on discourse analysis. In the context of the burgeoning of discourse analysis internationally, the field has been seriously neglected in Southern Africa. Studies of discourse are, we believe, vital to advancing our knowledge of inter-ethnic communication and understanding, an area that cannot be ignored in Southern Africa. In more general terms, I hope that this thesis represents a challenge to linguistic inquiry in ways that we have already outlined above. Most importantly, is that while it appears that most South African linguists are satisfied with adopting a rigid monotheoretical approach, I differ, advocating a multitheoretical perspective. This, I believe, allows a greater and more holistic view not only of the 'data' in question but also in terms of the general nature of inquiry, as well as the 'world' it attempts to describe. The body of this thesis is divided into two sections which reflect the two central concerns we have outlined above. Section A, divided into three chapters, is chiefly concerned with the conceptual basis of Xhosa narrative and its linguistic manifestation. In this section we shall find cause to query and to redefine traditional approaches to the linguistic categories manifest in Xhosa narrative. In section B, also divided into three chapters, we shall be concerned with the development of a theory of narrative production with specific reference to intsomi production. In this section we include an in depth criticism of previous approaches to this problem before developing and applying our own theory. There are two appendices attached to this thesis. The first presents certain tables and figures relevant to chapter 4. while the second includes the narrative texts from which we draw our examples. (Introduction, p. 21-22)
Keywords: Folk literature, Xhosa; Xhosa language -- Spoken Xhosa